2018
DOI: 10.2478/sm-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Personality Types and Strategy Choices in Foreign Language Learning

Abstract: Language learning is a comprehensive concept with its components and needs. Because of this reason, it is affected by various subjects, most significant two of which are learner personality and language learning strategy choices of the students. By taking into consideration the importance of these factors in language education, the main aim of this study is to find out the relationship of students' personality types and their language learning strategy choices by also taking into account their language levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Extraverts are interested in faster and less accurate methods, and they are inclined to talk thoughtlessly. Mutlu ( 2018 ) investigated the relationship between communication strategies and personality types. He found that personality types are not significantly correlated with learners' use of strategy types.…”
Section: Major Concepts On the Spotlightmentioning
confidence: 99%
“…Extraverts are interested in faster and less accurate methods, and they are inclined to talk thoughtlessly. Mutlu ( 2018 ) investigated the relationship between communication strategies and personality types. He found that personality types are not significantly correlated with learners' use of strategy types.…”
Section: Major Concepts On the Spotlightmentioning
confidence: 99%